Community Litter Arthropods Associated cerrado and gallery forest, in the Ecological Station Sierra Das Araras - Mato Grosso, Brazil (Revista Brasileira Multidisciplinar, 2010)
The litter arthropod fauna distinguishes itself by its importance in nutrient cycling and organic matter degradation. This invertebrate fauna has been emphasized as crucial for the processes that structure ecosystems. This study aims to evaluate and compare the arthropod fauna composition, richness and abundance in litter of two environments: the savanna and the gallery forest at Serra das Araras Ecological Station , Mato Grosso. To collect the arthropods a 120m transects for each habitat was delimited, divided into six points in each environment. For all the litter collection points, we marked a plot measuring 1.0 x 1.0 m, totalizing 6m2 for an environment, where the arthropods found were identified by order level, and the individuals were grouped into morphospecies. The total arthropods richness found in the savanna and in the gallery forest areas was 38 morphospecies, 28 morphospecies were found in the savanna and 20 in the gallery forest, with total abundance of 381 individuals, being 226 individuals collected in the savanna and 155 individuals in the gallery forest. The more abundant morphospecies in the savanna and gallery forest belonged to Hymenoptera and Isoptera orders, with 10 and 4 morphospecies and abundance of 263 and 78 individuals respectively. The greatest organism richness and abundance occurred in the savanna, because it is a tropical environment with the greatest biodiversity, especially regarding its insect fauna, and this diversity is primarily concerned with the variety of habitats that the environment provides , which gives the species shelter, food and reproduction sites.
Keywords: Savanna; Biodiversity; Arthropods.